Meningkatkan Kemampuan Peserta Didik Dalam Literasi Dan Numerasi Serta Adaptasi Teknologi Di SDN Menampu 02 Melalui Program Kampus Mengajar Angkatan 6 - Afifa Ulin Nukha; Astri Widyaruli A (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The Teaching Campus embodies part of the educational learning program in basic education units, the Merdeka Belajar Kampus Merdeka (MBKM) activity, which provides students with classroom learning experiences by partnering with educators in learning methods in primary and secondary education units. In other words, the Teaching Campus activities realize the Independent Campus goal by providing opportunities for students to learn and grow through programs outside the classroom. This research uses a qualitative approach with a descriptive method. Qualitative research is an analysis carried out to find out and describe existing events and evidence by describing them in the form of data, images and text. Basic education embodies the basic education phase for children aged 6 to 12 years which is developed according to educational units, basic expectations and social culture. Students from Muhammadiyah University and Jember University Jember who are studying for the Class 6 Teaching Campus Program are currently undergoing a number of work programs. One of them is related to literacy and numeracy in the Regional Technical Implementation Unit (UPTD) SDN Menampu 02 education unit.